Hypothesizing a New Case Study House Program: A Systems Approach - Genevieve Baudoin (Oz, 2014)
In 1945, Arts and Architecture announced that they would be publishing the designs of eight case study houses that envisioned the “house—post war.” These infamous Case Study Houses grew from an initial eight to thirty-six designs over twenty-two years—some built, some imagined.